2020
DOI: 10.3390/biomimetics5030037
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis Investigate Pulmonary Autograft Root and Leaflet Stresses to Understand Late Durability of Ross Operation

Abstract: Ross operation might be a valid option for congenital and acquired left ventricular outflow tract disease in selected cases. As the pulmonary autograft is a living substitute for the aortic root that bioinspired the Ross operation, we have created an experimental animal model in which the vital capacity of the pulmonary autograft (PA) has been studied during physiological growth. The present study aims to determine any increased stresses in PA root and leaflet compared to the similar components of the native a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…For example, the full inclusion of PA is not uncommon in patients with a tendency to progressive dilatation of the implanted conduit or those with poorly controlled blood pressures that may be too high and disabling for the PA [ 1 6 , 8 , 40 , 43 , 57 ]. However, these patients who exhibit disorders of the connective tissue structure can potentially have a reduced benefit from use by the Ross procedure because once the PA is encased in the rigid dacron prosthesis, its mobility is greatly reduced with a detrimental effect on the function of the PA as a living tissue [ 18 20 , 60 ]. For these recipients of the Ross procedure, although not ideal candidates and for whom the use of PA is not discouraged, implant failure may occur, as shown with the reoperation rate ranging from 20% to 50%—still considered low—and between 1% and 2% per patient-year [ 37 , 41 , 49 ].…”
Section: When To Use or Not To Use The Pulmonary Autograftmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the full inclusion of PA is not uncommon in patients with a tendency to progressive dilatation of the implanted conduit or those with poorly controlled blood pressures that may be too high and disabling for the PA [ 1 6 , 8 , 40 , 43 , 57 ]. However, these patients who exhibit disorders of the connective tissue structure can potentially have a reduced benefit from use by the Ross procedure because once the PA is encased in the rigid dacron prosthesis, its mobility is greatly reduced with a detrimental effect on the function of the PA as a living tissue [ 18 20 , 60 ]. For these recipients of the Ross procedure, although not ideal candidates and for whom the use of PA is not discouraged, implant failure may occur, as shown with the reoperation rate ranging from 20% to 50%—still considered low—and between 1% and 2% per patient-year [ 37 , 41 , 49 ].…”
Section: When To Use or Not To Use The Pulmonary Autograftmentioning
confidence: 99%
“…Several studies have reported a very high and hardly acceptable rate of reoperations for pulmonary autograft expansion [ 29 , 30 , 33 ]. It is important to underline that in recipients of Ross procedures who experience the PA dilation leading to aortic insufficiency, the increase in the diameter of the neoaortic root occurs at the time of discharge from the hospital, suggesting the existence of technical problems related to the procedure [ 11 , 12 , 18 21 ]. Surgeons with more experience in using the Ross procedure have pointed out that technical improvements reduce the risk of pulmonary autograft dilation.…”
Section: When To Use or Not To Use The Pulmonary Autograftmentioning
confidence: 99%
See 1 more Smart Citation
“…The study and the application of cellular technologies for repairing bone defects is a multidisciplinary task that does not merely require research in the field of directed differentiation and cell growth, but also the search for optimal materials to create a solid framework for bioengineering design [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…This research question has been studied by several, and it continues in this manuscript 2 from Dr Elaine Tseng's group at University of California San Francisco, in collaboration with the clinical Ross program of Dr Ismail Elhahamsy at Montreal Heart Institute and Mt Sinai Hospital. [3][4][5] The authors sought to examine autograft wall stresses after the Ross procedure using patient-specific material properties of the tissue. Several novel aspects make it a commendable effort toward a better understanding of autograft remodeling and dilatation.…”
mentioning
confidence: 99%